Green Product Innovation, Green Process Innovation, and its Impact on Green Performance of Batik SMEs - Nuryakin Nuryakin (Benefit: Jurnal Manajemen dan Bisnis, 2022)
This study aims to analyze the effect of green product innovation and green process innovation on the green performance of SMEs. The data of this study were collected from Batik SMEs in Yogyakarta Regency, Indonesia, with 204 Batik SMEs’ owners. This research used purposive sampling methods for the data process collecting. The result of this study uncovered that green product innovation had a significant positive effect on the green performance of SMEs. Green process innovation had a positive effect on the performance of SMEs.